• Упрости выражение:
    [tex]4 \times (3 - \frac{2}{5} x) - 2(0.6x + \frac{3}{4})[/tex]

Ответы 2

  •  4*(3-\frac{2}{5}x)-2*(0.6x+\frac{3}{4})= 12-1.6x-1.2x-1.5=-2.8x+10.5
    • Автор:

      beard
    • 5 лет назад
    • 0
  • 4( 3 - 2/5х ) - 2( 0,6х + 3/4 ) = 10,5 - 2,8х.2/5 = 2 × 2 / 5 × 2 = 4/10 = 0,4;3/4 = 3 × 25 / 4 × 25 = 75/100 = 0,75.Значит:4( 3 - 0,4х ) - 2( 0,6х + 0,75 ) = 12 - 1,6х - 1,2х - 1,5 = 12 - 1,5 - 1,6х - 1,2х = 10,5 - 2,8х.Ответ: 10,5 - 2,8х.
  • Добавить свой ответ

Еще вопросы

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years